The Idler's diary, 2009 - Hodgkinson, Tom (Cassell Illustrated, 2008)
This a diary like no other. With appointment pages interspersed with things to do, recipes, drawings, arcana, poems and other pearls of wisdom - the "Idler Diary" will help you gently float down river in 2009. Illustrated in glorious technicolour by the Idler's crack team of artists and cartoonists and with contributions for a nationwide team of well known slackers. Illuminating, irreverent and intriguing, this is the perfect gift for daydreamers everywhere. It includes a full list of all medieval feast days.